Impact of Mergers and Acquisitions on Employee Psychological Contract in Selected Glove Manufacturing Companies in Selangor, Malaysia - Lim, Chee Lip (2024)
Mergers and Acquisitions (M&A) represent pivotal corporate manoeuvres designed to enhance business growth, market competitiveness, and financial gains. The glove manufacturing sector in Malaysia has experienced a notable surge in M&A activities in recent years. Although these strategic undertakings hold the potential for considerable corporate advantages, they also bear a substantial impact on the psychological contracts of employees. The psychological contract embodies the tacit set of expectations, perspectives, and convictions held between employees and employers. It covers the perceived mutual commitments, assurances, and collective understandings within the employment bond. These contracts, though unspoken and not codified in formal documents, are derived from interactions, the organization's ethos, and its policies and practices. Essentially, psychological contracts mirror employees' personal beliefs about their anticipated benefits from the employer, alongside their own contributions. Expectations might span job stability, career progression opportunities, acknowledgment, work-life harmony, and the broader work experience. The nature of a psychological contract is fluid, adjusting with shifts in the workplace, policy modifications, leadership changes, and personal employee journeys. Effectively navigating and honouring these contracts is vital for nurturing positive employee engagement, contentment, and organizational triumph. When employees' preconceptions are met by their actual work experiences, it fosters a thriving and efficient workplace. Conversely, discrepancies or breaches of the psychological contract can precipitate employee discontent, sagging morale, and waning organizational allegiance. This study delves into the effects of mergers and acquisitions (M&A) on the psychological contracts of employees in Selangor, Malaysia's glove manufacturing industry. As M&A becomes increasingly commonplace in today's fast-evolving business milieu, it's imperative to scrutinize its impact on the fabric of the employer-employee relationship. The inquiry is set against the backdrop of Selangor's glove industry, a sector of significant economic weight, and examines how corporate amalgamations may reshape the workforce's landscape. The analysis of the interplay between a range of elements and the facets of the psychological contract amid mergers and acquisitions (M&A) has yielded insightful revelations. Within the cognitive realm, components such as supportive interrelations, supervisory and peer backing, along with a sense of fairness, are found to bolster psychological well-being and presence, thereby fostering employee engagement. Conversely, detrimental elements like workplace aggression, high staff turnover, stress, and subpar performance impinge upon the affective aspect, eroding employee dedication. Moreover, efficacious dialogue, personal convictions of the workforce, and the practice of mindfulness contribute positively to the affective sphere. In terms of behaviour, the working milieu’s factors, including supervisory and collective organizational backing, are pivotal in shaping staff conduct. M&A activities precipitate profound alterations in behaviour, amplifying collaborative efforts and cultivating a culture of enhanced transparency within teams. The research underscores the complex nature of psychological contracts during periods of M&A, offering key strategies for guiding employees through these organizational changes. The establishment of nurturing relationships, the assurance of fairness, the resolution of workplace conflicts, and the advancement of transparent communication and mindfulness are identified as vital to the successful navigation of M&As. By attentively managing these facets of the psychological contract, organizations can secure a positive and engaging employee experience and maintain steadfast dedication during times of transition. While the cross-sectional design of this study may introduce common method bias, constraints within the organizational setting limited the methodology choices. Nevertheless, the study's practical findings reveal that M&A activities exert a considerable impact on how individuals perceive their employment relationship. Employees adept at navigating organizational changes tend to perceive their psychological contract as evolving into a revised, and sometimes less advantageous, one. Therefore, it becomes imperative for organizational leaders to actively foster employees' adaptability to change, thus shielding them from the potential negative impacts of M&A. This paper contributes unique insights into the shifts in psychological contracts post-M&A, particularly within the glove manufacturing industry, with a special emphasis on the experiences of mid level employees.